How to succeed in the second-hand luxury market : the case of Portugal - Elias, Mariana dos Santos (2020)
The aim of this research is to understand which dimensions should be taken into consideration in order for luxury resale businesses to be successful in Portugal. To investigate this, a qualitative approach is used and four Portuguese luxury resellers are studied. Our findings show that the dimensions of authenticity and good condition are what Portuguese consumers look for when buying second-hand luxury items. Their main motivations for those purchases are (1) lower price, (2) uniqueness, (3) sustainability and (4) lifestyle. The results also show that businesses on this market face specific challenges, namely a present second-hand stigma and market specific conditions such as market size, culture and lack of purchasing power. To overcome them, some solutions can be implemented: providing a true luxury experience, selecting strategic locations, using a mix between online and offline channels, and creating partnerships among local businesses and big brands. This research is relevant for both managers and marketers, and contributes to the understanding of the emergent trend of second-hand luxury.